Improved omission testing for understanding the relative contribution of volatiles and tastants to sweet and savoury flavours - Delime, Perrine (2015)
This research project fully defines and evaluates a new approach in sensory omission testing, based on the same-different test (ASTM E2139-05 2011) and the Thurstonian measure d′. The applications of this new approach were investigated to fully characterise sweet and savoury flavour models and to investigate interactions between flavour compounds. Panels of naïve assessors conducted a series of omission tests using both a strawberry (9 volatiles) and a savoury (10 volatiles) flavour model. Using the Thurstonian d′ as a measure of the sensitivity of the discrimination test, results showed that the new approach using the same-different test was more sensitive compared to the more traditional approach using the triangle test: the d′ values obtained using the same-different test were 1.2 to 3.5 times higher than the d′ values obtained using the triangle test. It was hypothesised that the evaluation of three samples in the triangle test generated additional noise related to carry-over, sensory fatigue and memory effects. In particular, the triangle test requires that the three successive stimulus sensations are stored into memory until the discrimination test has been completed. The same-different approach was then successfully applied to (i) determine the relative importance of individual volatiles in ortho- and retronasal flavours (ii) assess interactions between volatiles in mixtures, and (iii) investigate interactions between congruent tastes and aromas in flavours. Results showed that cis-3-hexen-1-ol, 4-hydroxy-2,5-dimethyl-3-furanone and ethyl butanoate play a key role in the strawberry flavour, while sulfur compounds play a major role in the savoury flavour. For both the sweet and the savoury flavours, orthonasal perception was more sensitive to the removal of individual volatiles and this was attributed to different efficiency in delivery to the olfactory receptors. The same-different approach highlighted synergistic, suppressive and blending interactions between volatiles within flavour mixtures. In particular, the presence of 4-hydroxy-2,5-dimethyl-3-furanone increased the assessor sensitivity to the removal of other individual volatiles in the savoury flavour. Cross-modal interactions were highlighted within the strawberry flavour, particularly where congruency between taste and aroma could be identified. The omission approach brings a novel contribution to sensory science as it allows further analyses and a deeper understanding of flavour. This study pioneers the use of the Thurstonian d′ for omission experiments, enabling the relative importance of the individual components of flavour perception to be determined.